Gallic Acid Reduces Blood Pressure and Attenuates Oxidative Stress and Cardiac Hypertrophy in Spontaneously Hypertensive Rats. Issue 1 (December 2017) - Jin, Li; Piao, Zhe; Sun, Simei; Liu, Bin; Kim, Gwi; Seok, Young; Lin, Ming; Ryu, Yuhee; Choi, Sin; Kee, Hae; Jeong, Myung
Abstract Gallic acid (GA) has been reported to have beneficial effects on cancer, vascular calcification, and diabetes-induced myocardial dysfunction. We hypothesized that GA controls hypertension via oxidative stress response regulation in an animal model for essential hypertension. Spontaneously hypertensive rats (SHRs) were administered GA for 16 weeks. GA treatment lowered elevated systolic blood pressure in SHRs through the inhibition of vascular contractility and components of the renin-angiotensin II system. In addition, GA administration reduced aortic wall thickness and body weight in SHRs. In SHRs, GA attenuated left ventricular hypertrophy and reduced the expression of cardiac-specific transcription factors. NADPH oxidase 2 (Nox2) and GATA4 mRNA expression was induced in SHR hearts and angiotensin II-treated H9c2 cells; this expression was downregulated by GA treatment. Nox2 promoter activity was increased by the synergistic action of GATA4 and Nkx2-5. GA seems to regulate oxidative stress by inhibiting the DNA binding activity of GATA4 in the rat Nox2 promoter. GA reduced the GATA4-induced Nox activity in SHRs and angiotensin II-treated H9c2 cells. GA administration reduced the elevation of malondialdehyde levels in heart tissue obtained from SHRs. These findings suggest that GA is a potential therapeutic agent for treating cardiac hypertrophy and oxidative stress in SHRs.